Anne's House of Dreams - Montgomery, L. M. (Lucy Maud), 1874-1942 (Salt Lake City, UT : Project Gutenberg, 1996)
"Anne's House of Dreams" by L. M. Montgomery is a novel published in 1917. The story follows Anne Shirley and Gilbert Blythe as newlyweds beginning their life together in Four Winds, Prince Edward Island. In their seaside home, they meet unforgettable neighbors including a lighthouse keeper, an outspoken spinster, and a woman trapped in a tragic marriage. Through joy and heartbreak, Anne discovers that even dreams must make room for life's unexpected turns. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Anne%27s_House_of_Dreams
Release date is 1996-05-01
Charles Keller. HTML version by Al Haines.
Keywords: Orphans -- Fiction; Young women -- Fiction; Friendship -- Fiction; Marriage -- Fiction; Country life -- Prince Edward Island -- Fiction; Prince Edward Island -- History -- 20th century -- Fiction; Canada -- History -- 1867-1914 -- Fiction; Shirley, Anne (Fictitious character) -- Fiction